Summary of 2013/14 Production Costs for Indian River Fresh Market Grapefruit and Southwest Florida Juice Oranges - Fritz Roka; Ariel Singerman; Ronald Muraro (EDIS)
This 10-page report, developed through interviews with growers who managed their own citrus groves, outlines the cost of production budgets for fresh grapefruit and juice oranges grown during the 2013/14 season. The Florida citrus industry is on a steep learning curve as it collectively tries to maintain economically sustainable fruit yields from HLB-infected trees. Growers are experimenting with new materials and management strategies to reduce psyllid populations and improve a tree’s overall nutritional health. As a result, production costs have increased threefold since 2004. Between the 2012/13 and the 2013/14 seasons, production costs increased 30% and 34% for fresh grapefruit and juice oranges, respectively. Since 2004, production costs for fresh grapefruit have increased 182%, while costs to grow juice oranges have increased 211%.